Alternating current properties of bulk- and nanosheet-graphitic carbon nitride compacts at elevated temperatures - Tosapol Maluangnont; Phieraya Pulphol; Kanokwan Chaithaweep; Klichchupong Dabsamut; Thawanrat Kobkeatthawin; Siwaporn Meejoo Smith; Adisak Boonchun; Naratip Vittayakorn (My University, 2023)
g-C 3 N 4 in bulk- and nanosheet-form display stable, weakly temperature dependent AC properties from 400 to 50 °C.
Keywords: Nanosheet; Exfoliation joint; Temperature coefficient; Dissipation factor; Thermal Stability; Ga2O3 and related materials